Issues of development of the insurance services market of Uzbekistan - Murtazaev Nurbek Rashidovich (THE INNOVATION ECONOMY, 2026)
This article discusses in detail the issues of further development of the financial market of Uzbekistan, expanding the coverage of the population with high-quality financial services, and support for insurance companiesInsurance is mentioned as an effective means of protecting the property interests of individuals and legal entities at all stages of human development.